A novel approach for air quality trend studies and its application to european urban environments: The ICARUS project. (15th March 2022) - Sakellaris, Ioannis A.; Bartzis, John G.; Neuhäuser, Julia; Friedrich, Rainer; Gotti, Alberto; Sarigiannis, Dimosthenis A.
Abstract: Future climatic change is expected to have a significant impact on local scale air quality. The quantification of such an impact is not a straightforward task if one takes into consideration the inherent uncertainties due to lack of accurate enough input data. It is more reliable to look for trends rather than absolute values on the relevant parameterization.In the frame of the European Project ICARUS, the present study aims at providing heat-wave and concentrations trends for the period 2001-2050, following the moderate Representative-Concentration-Pathway (RCP4.5), on major air pollutants (PM10, PM2.5, NO2, O3) in Europe, focusing on nine cities: Athens, Basel, Brno, Copenhagen/Roskilde, Ljubljana, Madrid, Milan, Stuttgart and Thessaloniki. A novel approach, based on weather clustering is inaugurated to study climate change by inducing air quality trends, allowing to introduce proper trend indicators and focus on targeted weather and air quality local simulations. The adopted clustering approach has been applied utilizing daily weather data of 50-year period (2001-2050).The detailed weather data were obtained from the Coordinated-Regional-Climate-Downscaling-Experiment (CORDEX).The Regional-Climate-Model INERIS-WRF331F data have been selected, using the EUR11 (10km resolution) horizontal domain projection. Representative days have been identified per cluster, per five years period, where a detailed (2x2km) atmospheric modeling has been performed using WRFChem model. Concerning emissions input, the USTUTT High-Resolution (1kmx1km) data produced within ICARUS, have been postprocessed.The study has provided interesting city dependent results, revealing among others the correlation between weather patterns with higher heat-wave events and elevated O3 concentrations strengthening the hypothesis that the greenhouse effect leads to intensification of the atmospheric photochemical activity. Highlights: The greenhouse effect is likely to be 'felt' even under a moderate climatic scenario such as RCP4.5. There is a correlation between weather patterns with higher heat wave events and elevated O3, NO2 and PM concentrations. For all cities, the clusters associated with elevated heat wave events and O3 concentrations show an increase. The clusters with elevated NO2 concentrations show an increase in: Stuttgart, Brno, Basel, Madrid and Ljubljana. Clusters associated with elevated PM show an increase only in Stuttgart and Madrid.